2023
DOI: 10.1186/s12985-023-01963-x
|View full text |Cite
|
Sign up to set email alerts
|

A noninvasive model discriminating significant histological changes in treatment-naive chronic hepatitis B patients with normal ALT

Abstract: Background Traditionally part of chronic hepatitis B (CHB) patients with normal alanine aminotransferase (ALT) are recommended to antiviral therapy referring to liver biopsy. However, liver biopsy is an invasive method with various potential complications. A noninvasive model was established in the study to evaluate liver histology and to identify the need of antiviral therapy. Methods A total of 614 liver biopsied CHB patients with ALT less than u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The association between HBV DNA levels and liver histopathological changes was evaluated using multivariate logistic regression models, both with and without adjustment for covariates that have been reported as potential risk factors in previous studies. These covariates include age, 17–19 sex, 20 ALT, 19,21 AST, 18 PLT, 19 ALP, 22 and GGT, 22 and the results were reported as odds ratios with corresponding 95% confidence intervals. In multivariate logistic regression analyses, we constructed four models: Model I, no confounders were adjusted; Model II, demographic characteristics (age and sex) were adjusted; Model III, the most commonly associated risk factors for liver histopathology changes were further adjusted on the basis of Model II; Model IV, all the confounders were adjusted.…”
Section: Methodsmentioning
confidence: 99%
“…The association between HBV DNA levels and liver histopathological changes was evaluated using multivariate logistic regression models, both with and without adjustment for covariates that have been reported as potential risk factors in previous studies. These covariates include age, 17–19 sex, 20 ALT, 19,21 AST, 18 PLT, 19 ALP, 22 and GGT, 22 and the results were reported as odds ratios with corresponding 95% confidence intervals. In multivariate logistic regression analyses, we constructed four models: Model I, no confounders were adjusted; Model II, demographic characteristics (age and sex) were adjusted; Model III, the most commonly associated risk factors for liver histopathology changes were further adjusted on the basis of Model II; Model IV, all the confounders were adjusted.…”
Section: Methodsmentioning
confidence: 99%
“…Guidelines on the use of non-invasive tests have been published by the European Association for the Study of the Liver [ 47 ], emphasising their value in diagnosing and classifying chronic liver disease. Numerous studies have demonstrated the accuracy with which non-invasive models, such as the FIB-4 and APRI indices [ 45 ], the ALT, Age, PLT, and LS model [ 48 ], the AAR, API, APRI, KING, Zeugma scores, and Hudu’s score [ 49 , 50 ], can evaluate liver histology and forecast substantial liver injury. It has been discovered that these non-invasive models exhibit remarkable accuracy, with values of the area under the curve ranging from 0.595 to 0.870 [ 51 , 52 ].…”
Section: Prognostic Markersmentioning
confidence: 99%
“…Though these non-invasive diagnostics have shown potential, it needs to be noted that they ought to be employed together with clinical judgement as they could still not be able to replace liver biopsy. The conventional approach to determining the prognosis of CHB infection involves liver biopsy; however, there are several drawbacks to this method, including cost, potential problems, and invasiveness [ 45 , 48 , 49 ]. An alternate method that has benefits including becoming kinder to the body, safer, and more economical is to use non-invasive diagnostics [ 51 , 52 ].…”
Section: Prognostic Markersmentioning
confidence: 99%
“…Thus, ALT, AFP (alpha-fetoprotein) and platelet count were recently evaluated in a prognosis score for HCC in CHB (chronic hepatitis B) patients [9]. Another study shows that ALT, AFP, age, and liver stiffness are part of an evaluation score for liver damage in CHB with normal ALT levels [10]. RDW (red cell distribution width), together with other cellular ratios, was also used in predicting patient survival in CHB subjects with cirrhosis [11].…”
Section: Introductionmentioning
confidence: 99%